Inspiratory muscle training in pulmonary hypertension: TREMMI protocol - Leão, Marília Souza; Bergamascki, Lucas Mellaci; Xavier, Vivian Bertoni; Jaenisch, Rodrigo Boemo; Stirbulov, Roberto; Alves, Vera Lúcia dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Although the progressive nature of pulmonary hypertension (PH), including the impairment of respiratory muscle function, studies have demonstrated beneficial effects of physical exercise on the functional limitations caused by the disease in this population, being an important ally to the conventional drug therapy. There is no training protocol focused exclusively on respiratory musculature that is performed without supervision, since these patients have low adherence to the rehabilitation programs performed in an outpatient setting. Respiratory muscle training (RMT) improves functional capacity and quality of life (QoL) in patients with chronic diseases such as heart failure and COPD. However, the effects of an unsupervised RMT protocol on PH are not yet known. Objective: To developed an unsupervised, home-based RMT protocol for patients with PH. Methods: A double-blind, controlled, randomized clinical trial to evaluate the effectiveness of this protocol on respiratory muscle strength and endurance, functional capacity, by the six-minute walk test and QoL with the questionnaire The Medical Outcomes Study 36- item Short Form Health Survey (Sf-36) before and after an unsupervised training protocol and performed in a home environment with POWERbreathe. Two groups (IMT and SHAM) will be followed for 12 weeks with training performed 30 minutes daily. Results: We hope the intervention idealized by the protocol may will increase the respiratory muscle strength and endurance, the walk distance in six-minute walk test and QoL. Conclusions: Patients with PH who perform the intervention with inspiratory muscle training protocol may will be increase the respiratory muscle strength, functional capacity and QoL.